MARGINALIZATION OF SMALL RETAILERS AS A CONSEQUENCE OFTHE GROWTH OF MINIMARKET IN DENPASAR CITY - Adnyana, I Wayan (E-Journal of Cultural Studies; Volume 6, Number 2, Agustus 2013, 2013)
The growth of minimarket, especially the Circle K Minimarket in Denpasar City has been so fast that small retailers with their limitations have been getting left behind. This present study explored the marginalization of the small retailer as a consequence of the growth of the Circle K Minimarket in Denpasar City. It was conducted to identify the forms of the marginalization of the small retailer as a consequence of the growth of the Circle K Minimarket in Denpasar City. The theory of generative structure proposed by Bourdieu and the theory of power and knowledge proposed by Foucault were used eclectically to answer the problems of the study. Qualitative research method with the approach of cultural studies was employed. The data were collected through observation, in-depth interview, and documentation study. The data were descriptively, qualitatively and interpretatively analyzed. The result of the study showed that as a consequence of the growth of the Circle K Minimarket the small retailers became marginalized in economy; business network; technology; management; and socio-politics.
Keywords: marginalization, small trader, Circle K minimarket.